The angiotensin‐converting enzyme insertion/deletion polymorphism rs4340 associates with habitual physical activity among European American adults - Bruneau, Michael; Angelopoulos, Theodore J.; Gordon, Paul; Moyna, Niall; Visich, Paul; Zoeller, Robert; Seip, Rick; Bilbie, Stephen; Thompson, Paul; Devaney, Joseph; Gordish‐Dressman, Heather; Hoffman, Eric; et al. (Molecular genetics & genomic medicine, 2017)
Background The angiotensin‐converting enzyme (ACE) insertion/deletion (I/D) polymorphism (rs4340) (ACE DIP) accounts for half of the variability in plasma ACE concentrations. ACE has been widely studied for its influence on sports performance; however, research on its influence in physical activity is limited and inconsistent. We examined the influence of the ACE DIP on physical activity among 461 European Americans. Methods Subjects completed the Paffenbarger Physical Activity Questionnaire for weekly walking distance. Multivariate analysis of covariance (MANCOVA) tested log‐transformed differences in weekly walking distance among ACE DIP genotypes (II, ID, DD) with gender as a fixed factor, and age and body mass index (BMI) as covariates. Because we found a significant ACE DIPxBMI interaction (P = 0.03), we categorized the sample by normal weight (NW: BMI<25.0 kg/m2) and overweight (OW: BMI ≥25.0 kg/m2) and repeated the MANCOVA with multiple comparison adjustments. Results NW adults with ACE II walked 15.8 ± 11.1 km/week, ID 13.2 ± 10.6 km/week, and DD 17.9 ± 13.0 km/week, with ID walking less than II (P = 0.03) and DD (P = 0.01). OW adults with ACE II walked 16.7 ± 12.6 km/week, ID 13.8 ± 11.6 km/week, and DD 9.7 ± 9.0 km/week, with DD walking less than II (P = 0.02). Weekly walking distance was 8.2 ± 2.4 km/week less among OW adults with ACE DD than NW (P = 0.02). Conclusion BMI interacted with ACE DD such that OW walked ~8.2 km/week less than NW, potentially equating to a body weight differential of ~3.5 kg annually. The manuscript highlights our investigation of the angiotensin‐converting enzyme insertion/deletion polymorphism (ACE DIP) rs4340 and its association with habitual physical activity among a large sample of 461 European American adults. We found body mass index (BMI) interacted with the DD genotype of the ACE DIP and accounted for a 8.2 km/week difference between adults classified as normal weight and overweight. We feel this finding is novel and has clinical significance that could potentially equate to a body weight differential of ~3.5 kg per year.